Education Business Incubation Model as a Drive for Innovation and Strengthening Elementary School Independence (International Journal of Education and Literature, 2025)
Educational business incubation has become an important strategy for strengthening independence and innovation in elementary schools in the era of educational transformation. This approach allows schools to function not only as teaching institutions but also as centers for community-based economic and social empowerment. This study employs the Systematic Literature Review (SLR) method to analyze various scientific publications related to the implementation of educational business incubation, edupreneurship, and the strengthening of elementary school institutions. The findings indicate that educational business incubation programs can create alternative funding sources, expand opportunities for innovative learning, and reinforce a participatory culture within schools. Beyond financial aspects, business incubation also promotes cross-sector collaboration among schools, government, private sectors, and communities, thereby establishing a sustainable edupreneurship ecosystem. Through strategic and collaborative management, elementary schools can become independent, innovative institutions with high competitiveness in facing future educational challenges.